Sykepleiestudentenes kliniske praksis – om klinisk læringsmiljø og studenttilfredshet - Andreasen, Eva Mari; Høigaard, Rune; Haraldstad, Kristin (Nordisk Tidsskrift for Helseforskning, 2020)
Nurse practice – clinical learning environment and student satisfaction The purpose of this study was to investigate nursing students’ satisfaction with the clinical learning environment during clinical practice. A questionnaire was distributed to nursing students at a university (N=250) in Norway. Student satisfaction, task orientation, pedagogical atmosphere, supervisory relationship, and the premises of nursing on the ward were measured. Of the 250 students invited, 163 (66 %) completed the survey. Nursing students were largely satisfied with their clinical placement experiences, but they were more satisfied with hospital placements than home care placements. Supervision more than once a week and having one supervisor was important for student satisfaction. Students’ relationship with their supervisors was strongest associated with satisfaction with their clinical placements. Supervisors play an important role in nursing students’ satisfaction with their clinical practice, with results indicating that this should be emphasized in the development of nursing education. The results indicate that nursing guidance skills should be strengthened to ensure the quality of clinical placements in nursing education.